Regeneration of bone defect using micro-bioceramic PLLA polymer scaffolds synthesized by nonsolvent and solvent method - Park, Min-Sung; Jung, Youngmee; Kim, Soo Hyun; Kim, Sang-Heon; Kim, Young Ha; Min, Byoung Goo; Lee, Jin Woo (ASBM7: ADVANCED BIOMATERIALS VII, 2007)
Poly-L-lactic acid (PLLA) is a desirable and very attractive polymer for fabricating porous scaffolds. As of now, a solvent casting method with organic solvents has been used in scaffold fabrication process. However, residual organic solvents in the scaffolds have the problems of decreasing the effect of osteogenic induction due to the hindrance of bioceramic by polymer solution and it's harmfulness in vivo. To avoid these disadvantages of scaffolds by organic solvent casting method, we developed a new method fabricating polymer (PLLA)/ceramic (beta-TCP) composite scaffolds by baking method without using solvent, and then we tested properties of scaffolds on animals. As the result, non-toxicity has been proved through animal experiment and newly fabricated polymer/ceramic composites by a novel sintering method were induced rapid bone regeneration through enhancing the interaction of cells and a bone induction factor without any host immune response.